Sistem Informasi Berbasis Web Perbaikan Inventaris PLN ULP Helvetia - Ananda, Surizky; Maulana Ihsan (Jurnal Media Teknik Elektro dan Komputer, 2024)
This study develops a web-based system to support the repair and handling of damaged items at the Helvetia Customer Service Unit (ULP) of PLN. Previously, the recording and monitoring of damaged items at ULP Helvetia were conducted manually, often resulting in repair delays and inaccurate information. This web-based system is designed to streamline the reporting, recording, and tracking processes of repair statuses in real-time. With a user-friendly interface, users can easily report damages, monitor repair statuses, and access the repair history of each item. Implementation results indicate that this system successfully improves work efficiency, reduces handling time, and provides more accurate data for management. This system is expected to enhance operational performance at ULP PLN Helvetia and can be implemented in other PLN units.